Akuntabilitas Pengelolaan Alokasi Dana Desa di Desa Putatnganten Kecamatan Karangrayung Kabupaten Grobogan - Ayu Azizatut Takhia; Ahmad Sahri Romadon (STIE PENA, 2026)
This research was conducted with the aim of describing the accountability in the management of Village Fund Allocation (ADD) in Putatnganten Village, Karangrayung District, Grobogan Regency. Accountability is one of the main principles in good governance, especially in the management of village finances that are transparent, participatory, and accountable. The method used in this study is a qualitative descriptive case study. Data collection in this research was carried out through in-depth interviews, direct observation, and documentation. The credibility of the data was tested using triangulation of data sources and triangulation of data collection techniques. The sources of information were obtained through in-depth interviews involving three participants with seven questions. The results of the study show that the management of ADD in Putatnganten Village has been running quite well, indicating transparency in planning, implementation, and budget reporting. The village government involves the community in the deliberation process and reports activity realization through village information media. However, several obstacles remain, such as limitations in the capacity of village officials and suboptimal supervision from related institutions. Therefore, it is necessary to improve human resource capacity and strengthen supervision mechanisms to achieve more accountable and sustainable ADD management. Keywords: Accountability, Village Fund Allocation (ADD)